A molecular biology platform for the production of cytokines and cytokine-functionalized materials - Gonçalves, Anabela Ferreira (2019)
Leukemia inhibitory factor (LIF) and Oncostatin-M (OSM) are two pleiotropic cytokines from the IL-6 cytokine family with implications in health and disease. Their biotechnological exploitation finds applications in the treatment of different diseases such as cardiac and neurological pathologies, and even cancer. In recent years, several patents and research papers were published regarding their heterologous expression, however problems with production yield, protein stability and activity can significantly hinder the applicability of these cytokines. In this work, we developed a molecular biology platform for the cloning of cytokines LIF or OSM with different recombinant protein-based polymers aiming at their production and subsequent processing into functional materials. As polymers, we used a variant of an elastin-like recombinamer (ELR) and another from silk elastin-like proteins (SELPs). A combination of ELR-intein proteins was used as production, purification and cleavage tag for the cytokines, which can be encapsulated into organic and inorganic particles. On the other hand, a SELP-6xGlycine module was devised to facilitate further processing into a variety of different materials including films, fibres and scaffolds. In this system, we cloned both murine and human forms of the cytokines, to allow their use in different studies and models. Heterologous protein expression studies, using Escherichia coli as cell factory, indicate that all the designed proteins are overexpressed although at different levels depending on the nature of the cytokine, though always suitable for lab-scale utilization. We believe that the modular system here discussed will endow us with sufficient plasticity to design materials adjusted to the pathologies where LIF and OSM are implicated and may have a positive therapeutic impact.